A review on current advances in the energy and environmental performance of buildings towards a more sustainable built environment - Soares, N. (2017)
Nowadays, debates addressing climate change, fossil fuels depletion and energy security highlight the need for a more sustainable built environment in order to reduce energy consumption and emission trends in the buildings sector. Meeting these targets is a challenge that calls for innovative research to improve the use of renewable energy sources, new technologies, and holistic tools and methodologies. Such research should integrate the dynamics and main drivers of energy supply and demand in buildings to support new policies, plans and actions towards lowering the built environment burdens. This paper brings together ten research topics concerning the energy and environmental performance of buildings, which can support a shift towards a more sustainable built environment. Background information and state of the art literature on the covered research topics is briefly summarized, gaps are identified and guidelines for future research are provided. The selected topics cover different stages along the lifetime of buildings (from design and operation, to retrofitting and end-of-life), different scale approaches (from building elements/components, to the building, district and urban scales), and different methods to assess the energy and environmental performance of buildings (life-cycle assessment, generative design methods and retrofitting tools). Other topics are discussed such as: nearly zero-energy buildings, the control of domestic energy resources in smart grid scenarios, the need to include end-users' behaviors in the dynamics of energy demand, the advantages of improving thermal storage by using phase change materials, the importance of reducing heating and cooling energy demand (maintaining indoor thermal comfort), and the optimization of heating and cooling fluids, and their system control.